(untitled) (Innovative professional education, 2025)
Important factors in the development of the economy are knowledge-intensive and high-tech industries. Specialists in these industries make a significant contribution to the production of gross domestic product, and it is their shortage that is particularly noticeable in Ukraine and throughout the world. The main reason for this deficit is the loss of popularity of scientific, technical, and engineering professions and, as a result, a decrease in the level of interest in studying natural, technological, and mathematical subjects among education seekers, as evidenced, in particular, by the negative dynamics of the number of graduates of general secondary education institutions who undergo external independent assessment in mathematics, physics, chemistry and biology.